2018
DOI: 10.5935/2595-0118.20180039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cognitive impairment in patients with episodic migraine

Abstract: BACKGROUND AND OBJECTIVES: The purpose of this study was to evaluate the presence of cognitive deficits in patients with episodic migraine and control group, and to compare with the results previously described in the literature. METHODS: Patients with episodic migraine were included according to the International Headache Society criteria, and a control group was selected, matched by sex, age, and schooling. Patients were asked about the frequency and intensity of headaches, medications used, and comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…O risco de lesões apresenta-se tanto para pacientes com aura como sem aura, ocorrendo um aumento em pacientes com migrânea crônica e migrânea com aura. Estudos demonstraram efeitos cumulativos da migrânea no sistema nervoso central (SNC), embora esses resultados ainda não sejam bem esclarecidos, acredita-se que em longo prazo, as lesões provocadas pela migrânea causam déficits cognitivos (TEIXEIRA et al, 2018).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O risco de lesões apresenta-se tanto para pacientes com aura como sem aura, ocorrendo um aumento em pacientes com migrânea crônica e migrânea com aura. Estudos demonstraram efeitos cumulativos da migrânea no sistema nervoso central (SNC), embora esses resultados ainda não sejam bem esclarecidos, acredita-se que em longo prazo, as lesões provocadas pela migrânea causam déficits cognitivos (TEIXEIRA et al, 2018).…”
Section: Resultsunclassified
“…A migrânea é uma dor craniana com duração de 4 a 72 horas, definida por muita intensidade, pulsátil ou latejante, que piora durante as atividades diárias, podendo apresentar sintomas como náuseas, fotofobia, fonofobia e vômitos. Numa crise típica de migrânea podem ocorrer cinco fases detectáveis, como por exemplo, pródromo (sintomas premonitórios), cefaleia, aura, sintomas associados à dor (náuseas e fotofobia) e pósdromo (exaustão e fadiga) (TEIXEIRA et al, 2018).…”
Section: Introductionunclassified
“…[ 19 20 ] However, few clinic-based studies reported negative results. [ 18 23 24 25 ] The conflicting results may be due to the small sample size in these studies (ranging from 12 to 74), different study designs such as the inclusion of older patients,[ 23 24 25 ] recruitment of specific groups such as college students,[ 25 ] use of different cognitive test batteries,[ 24 25 ] not controlling for the proximity of the attack,[ 23 25 ] and use of different techniques of analysis of results. Most studies did not mention whether preventive medications were continued during the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Studies using Montreal cognitive assessment reported positive results in discriminating migraine patients from controls,[ 26 28 29 30 ] except in one. [ 25 ] These differences suggest possible greater impairment of frontal lobe functions than other cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…O risco de lesões apresenta-se tanto para pacientes com aura como sem aura, ocorrendo um aumento em pacientes com migrânea crônica e migrânea com aura. Estudos demonstraram efeitos cumulativos da migrânea no sistema nervoso central (SNC), embora esses resultados ainda não sejam bem esclarecidos, acredita-se que em longo prazo, as lesões provocadas pela migrânea causam déficits cognitivos(TEIXEIRA et al, 2018). Osmofobia e odor como gatilho de cefaleia são condições muito frequentemente associadas a migrânea.…”
unclassified